1988
DOI: 10.1111/j.1524-4725.1988.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Metastases from Laryngeal Carcinoma

Abstract: The authors describe a case of cutaneous metastases from a squamous cell carcinoma of the laryngeal vestibule. The skin lesions, which consisted of nodules localized to the forehead and left arm, appeared 2 years after diagnosis of the primary tumor. The skin manifestations preceded lung metastases by 5 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The site of skin metastases include neck, chest, scalp, face, lips, axilla, areola, back, arms, and digits, with the most common being the neck and chest. [910] The skin metastases may evolve through three possible mechanisms, direct spread via tissue planes, local spread through dermal lymphatic's, and distant spread as a result of hematogenous spread. [11] Cutaneous metastases from laryngeal carcinoma may present as non-tender firm nodules, as sclerodermoid lesions, or may mimic an inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The site of skin metastases include neck, chest, scalp, face, lips, axilla, areola, back, arms, and digits, with the most common being the neck and chest. [910] The skin metastases may evolve through three possible mechanisms, direct spread via tissue planes, local spread through dermal lymphatic's, and distant spread as a result of hematogenous spread. [11] Cutaneous metastases from laryngeal carcinoma may present as non-tender firm nodules, as sclerodermoid lesions, or may mimic an inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Veraldi reported a case with metastatic laryngeal tumor in the form of localized nodules in frontal area and arm in a patient with laryngeal tumor. [9] Bottoni reported a patient with metastatic laryngeal carcinoma in the form of infiltrate erythema in supra and infra clavicular regions after 4 years of primary surgical treatment. As cutaneous metastases in cases of carcinoma larynx can be solitary or multiple, therefore FDG PET CT has an added benefit in knowing the extent of disease as well as sites of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Review of the surgical literature revealed only seven previously reported cases of cutaneous metastases from squamous cell carcinoma of the larynx. [78]…”
Section: Discussionmentioning
confidence: 99%
“…[79] It is evident on literature search that multiple metastases from a laryngeal carcinoma involving all five distal phalanges, bilateral lung, liver and multiple subcutaneous nodule in upper and lower extremities, as described above is not reported till date.…”
Section: Discussionmentioning
confidence: 99%
“…[9] A review of the surgical literature revealed only seven previously reported cases of cutaneous metastases from squamous cell carcinoma of the larynx. [1011] The common sites of cutaneous metastasis include neck, chest, scalp, face, lips, axilla, areola, back, arms, and digits. It is evident on the literature search that multiple metastases from laryngeal carcinoma involving all five distal phalanges of hand, bilateral lungs, and liver have not been reported till date.…”
Section: Discussionmentioning
confidence: 99%